Austerity urbanism and Olympic counter-legacies: Gendering, defending and expanding the urban commons in East London. (October 2018) - Gillespie, Tom; Hardy, Kate; Watt, Paul
This article reflects on an occupation led by single mothers to contest the destruction of social housing in post-Olympics East London. In the process, it argues for a more gendered theorisation of the urban commons. Drawing on auto-ethnography, participant observation and qualitative interviews, the article argues three central points: First, that the occupation demonstrates the gendered nature of the urban commons and the leadership of women in defending them from enclosure; second that the defence of an existing urban commons enabled the creation of a new temporary commons characterised by the collectivisation of gendered socially reproductive activities; and third that this commoning has had a lasting impact on housing activism at the city scale and beyond. This impact is conceptualised as an 'Olympic counter-legacy' that is characterised by the forging of new relationships and affinities, the strengthening of networked activism and circulation of tactics between campaign groups.